Lack of Pathogenic Germline DICER1 Variants in Males with Testicular Germ-Cell Tumors - Vasta, Lauren M. (Cancer Genet, 2020)
BACKGROUND: Several studies have reported conflicting evidence on the inclusion of testicular germ cell tumors (TGCT) in the DICER1 tumor-predisposition phenotype. We evaluated the relationship between DICER1 and TGCT by reviewing scrotal ultrasounds of males with pathogenic germline variants in DICER1 and queried exome data from TGCT-affected men for DICER1 variants. METHODOLOGY: Fifty-four male DICER1-carriers and family controls (n=41) enrolled in the National Cancer Institute (NCI) DICER1 Natural History Study were offered scrotal ultrasounds. These studies were examined by a single radiologist for abnormalities. In parallel, DICER1 variants from two large exome-sequenced TGCT cohorts were extracted. We used previously published AMG-AMP criteria to characterize rare DICER1 variants. RESULTS: There was no observed difference in frequency of testicular cystic structures in DICER1-carriers versus controls. DICER1 variation was not associated with TGCT in the NCI DICER1-carriers. In 1,264 exome-sequenced men with TGCT, none harbored ClinVar- or InterVar-determined pathogenic or likely pathogenic variants in DICER1. Three DICER1 variants of uncertain significance (one case and two controls) were predicted “damaging” based on a priori criteria. CONCLUSION: Using two complementary approaches, we found no evidence of an association between pathogenic DICER1 variants and TGCT.